How Does Volatility of Characteristics-sorted Portfolios Respond to Macroeconomic Volatility? - Al Samman, Ahmed; Otaify, Mahmoud Moustafa (International Journal of Economics and Financial Issues, 2017)
This paper investigates how volatility of characteristics-sorted portfolios respond to macroeconomic volatility based on Egyptian data covering the period July 2002 – June 2015. The paper uses three characteristics, namely size, book-to-market ratio and financial leverage to sort the most active stocks into corresponding characteristics mimicking portfolios. We examine how volatility of single characteristic mimicking portfolios as well as double characteristics mimicking portfolios respond to volatility in macroeconomic variables. The results indicate that the money supply volatility is the dominant source of volatility for the characteristics-sorted portfolios, followed by the inflation volatility. Both investors and policy makers should consider the volatility of money more than the interest rate channel in rebalancing their portfolios and formulating policies. Arguably, the low-frequency volatility of many portfolios tend to decrease during periods of global financial crisis and political uncertainty post the Egyptian revolution in 2011. Keywords: Characteristics-sorted portfolios, Macroeconomic Volatility, Spline-GARCH, Egyptian Exchange. JEL Classifications: G110, G120, G140